The Competence of Human Resources in Collage Graduate to Face Global Competition - Bukman Lian (Jurnal Dosen Universitas PGRI Palembang)
AbstractThe era of global competition these days had provided an opportunity and also threat for organization to be able to prepare to manage the organization into effective and efficient through good management human resources. Human resource that produced is supposed to have competence which capable of working based on its field. So the importance of competence human resources caused by competence, and it is one of the tools to attain a desired goal.Competence is the ability of an individual for executing a job properly and has a good quality based on such matters as knowledge, expertise, and attitude. So that‟s why human resources besides having the knowledge and expertise, it also need to have a good attitude that expected. If the combination of knowledge, expertise and attitude has not been realized so that the individual workers can be described as incompetence. The importance of competence makes the development of competence used as a basis fortraining, basic recruitment, performance measurement and basic award.Keywords: Global Competition, Competence, Human Resources, Collage Graduate